Examining the Role of HRM Practices to Enhance Employee Satisfaction: Mediating Role of Supply Chain Integration - Eny Lestari Widarni; Silvi Asna Prestianawati; Mahrinasari MS (International Journal of Supply Chain Management, 2020)
The main objective of the present study was to examine the impact of empowerment, compensation and training on satisfaction and supply chain integration. Moreover, the mediating role of supply chain integration between the impact of empowerment, compensation and training and satisfaction is examined as well. The data is collected from the employees of hotels in Indonesia through cluster sampling. The response rate of the present study was 68%. For the analysis purpose, PLS-SEM technique was used. The results revealed that employee satisfaction is directly impacted by empowerment, compensation and training and satisfaction; supply chain integration mediates as well between these relationships. The findings of the study are important for the practitioners of the supply chain in the hotel industry in developing strategies to enhance employee satisfaction through supply chain integration and other HRM Practices.